Frequency-Dependent Interictal Neuromagnetic Activities in Children With Benign Epilepsy With Centrotemporal Spikes: A Magnetoencephalography (MEG) Study - Zhang, Tingting; Shi, Qi; Li, Yihan; Gao, Yuan; Sun, Jintao; Miao, Ailiang; Wu, Caiyun; Chen, Qiqi; Hu, Zheng; Guo, Hu; Wang, Xiaoshan (Frontiers in Human Neuroscience, 2020)
Objective This study aimed to investigate interictal neuromagnetic activities in the low- to high-frequency ranges in children with benign epilepsy with centrotemporal spikes (BECTS), especially those without interictal epileptiform discharges (IEDs). Methods We studied 21 clinically-diagnosed BECTS patients and 11 age-matched healthy controls (HC) using high-sampling magnetoencephalography (MEG). Neuromagnetic sources were assessed with accumulated source imaging. The MEG data were analyzed in seven frequency bands. The MEG recordings distinguished BECTS without IEDs (n = 10) from those with IEDs (n = 11) and HC (n=11). Results At 1–4 Hz, the neuromagnetic activities in healthy subjects tended to locate at the precuneus/posterior cingulate, while those of the BECTS patients without IEDs tended to locate at the medial frontal cortex compared to BECTS patients with IED. The MEG source imaging at 30-80Hz revealed that BECTS patients without IEDs had higher occurrences of interictal brain activity in the medial temporal lobe compared to controls and the brain activity strength seemed to be weaker. There was a significant correlation between the source strength of the interictal gamma oscillations of BECTS patients without IEDs and the duration of epilepsy. Conclusions IEDs might disrupt the default mode network. Aberrant brain activities in BECTS patients without IEDs were associated with cognitive areas of the brain. The strength of gamma oscillations in the chronic epilepsy state reflected the duration of BECTS. Significance Low- and high-frequency MEG signals revealed different neuromagnetic activities in BECTS patients with and without IEDs. Gamma oscillations could be used to identify BECTS patients without IEDs.